The big red book of beginner books - Eastman, P. D. (Philip D.); Heilbroner, Joan.; Lopshire, Robert; McClintock, Mike.; Siebel, Fritz; Perkins, Al.; Gurney, Eric.; Sadler, Marilyn; Bollen, Roger (New York : Random House, 2009)
Six stories for beginning readers.
I want to be somebody new!! -- Sam and the firefly -- Stop that ball! -- Robert the rose horse -- The digging-est dog -- The very bad bunny.
An Easy Reader.
4+